2017
DOI: 10.1186/s12864-017-4293-2
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting patterns of evolutionary constraint and novelty revealed by comparative sperm proteomic analysis in Lepidoptera

Abstract: BackgroundRapid evolution is a hallmark of reproductive genetic systems and arises through the combined processes of sequence divergence, gene gain and loss, and changes in gene and protein expression. While studies aiming to disentangle the molecular ramifications of these processes are progressing, we still know little about the genetic basis of evolutionary transitions in reproductive systems. Here we conduct the first comparative analysis of sperm proteomes in Lepidoptera, a group that exhibits dichotomous… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 77 publications
2
33
0
Order By: Relevance
“…Recently, characterizations of the proteins found in lepidopteran sperm has opened a new avenue to assess their evolution and function (Whittington et al, 2017;Whittington, Zhao, Borziak, Walters, & Dorus, 2015). Proteomic studies have revealed distinct protein profiles for these two cell types (Whittington, Karr, Mongue, Walters, & Dorus, 2019).…”
mentioning
confidence: 99%
“…Recently, characterizations of the proteins found in lepidopteran sperm has opened a new avenue to assess their evolution and function (Whittington et al, 2017;Whittington, Zhao, Borziak, Walters, & Dorus, 2015). Proteomic studies have revealed distinct protein profiles for these two cell types (Whittington, Karr, Mongue, Walters, & Dorus, 2019).…”
mentioning
confidence: 99%
“…As discussed above, sperm competition should create a distinctive pattern of molecular evolution for involved proteins [16]. We perform the first molecular evolutionary analyses of dimorphic sperm, assessing patterns of both polymorphism and divergence among sperm proteins from both eupyrene and apyrene sperm using proteomic datasets of two species: the monarch butterfly, Danaus plexippus [42], and the Carolina sphinx moth, Manduca sexta [43]. North American monarchs spend time at incredibly high density in overwintering colonies in Mexico [44] and, owing to these unique population dynamics, have some of the highest female remating rates observed in Lepidoptera.…”
Section: Sperm Dimorphismmentioning
confidence: 99%
“…Next, we leveraged orthology, as established by Whittington et al [42], to test for differences in mating system while controlling for the effects of sperm proteome content. As substantial number of proteins, hereafter referred to as sperm homologs, are found in the sperm proteomes of both species and offer the opportunity to directly assess the selective pressures experienced by the same genes with conserved function but found in species with different levels of postcopulatory selection.…”
Section: Differences Between Sperm Proteins and The Background Genomementioning
confidence: 99%
See 1 more Smart Citation
“…Previous analyses of insect sperm proteomes have consistently identified proteins 328 generally considered to be SFPs (i.e. highly expressed in the MAG and believed to be 329 secreted molecules transferred to females as non-sperm components [32,62,63]. To 330 identify proteins predominantly produced by the MAG, but identified in both our sperm 331 and ejaculate sample, we used a 2.5-fold greater abundance threshold in the ejaculate 332 relative to sperm.…”
mentioning
confidence: 99%